2020
DOI: 10.1155/2020/7439506
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Yersinia enterocolitica O:3 Lipopolysaccharide in Collagen-Induced Arthritis

Abstract: Yersinia enterocolitica O:3 is mentioned among the most common arthritogenic pathogens. Bacterial components (including lipopolysaccharide (LPS)) may persist in the joint after eradication of infection. Having an adjuvant activity, LPS may enhance production of anticollagen antibodies, involved in the pathogenesis of rheumatoid arthritis. Furthermore, its ability to activate complement contributes to the inflammation. The aim of this work was to investigate whether Yersinia LPS (coinjected with collagen) is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Recently, we demonstrated that coinjection of collagen and lipopolysaccharide is not associated with the increase of anti-collagen antibody production in mice, excluding the involvement of adjuvant activity of LPS during experimental RA development [ 26 ]. Surprisingly, Yersinia LPS injection decreased anti-collagen antibody production (although insignificantly).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated that coinjection of collagen and lipopolysaccharide is not associated with the increase of anti-collagen antibody production in mice, excluding the involvement of adjuvant activity of LPS during experimental RA development [ 26 ]. Surprisingly, Yersinia LPS injection decreased anti-collagen antibody production (although insignificantly).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, Yersinia LPS injection decreased anti-collagen antibody production (although insignificantly). However, LPSs of all tested chemotypes were found to be potent immunogens themselves [ 26 ].…”
Section: Discussionmentioning
confidence: 99%